Micro electro mechanical system based sensor for Early detection of parkinson's disease – Design and simulation - GRK PRASAD,; N.SIDDAIAH,; K.SRINIVASA RAO,; P.S.SRINIVAS BABU, (International Journal of Pharma and Bio Sciences, 2017)
In this paper, a novel structure is proposed at Micro Level to detect the symptoms of Parkinson’s desease at an early stage. We have designed the proposed structure using Finite Element Method (FEM) tool, Comsol multi physics by utilizing capacitive actuation technique. The simulations are done on capacitive based micro structure by changing the material of proof mass and the force applied on proof mass. Also we have calculated and simulated the thermal variations and stress by thermal change on the legs of proposed structure. It is observed that Poly Tetra Fluro Ethylene material of the proof mass with silicon legs by giving specific dimensions are showing best optimized results. This result shows high sensitivity, high reliability and cost effectiveness of the proposed Parkinson’s Disease Sensor.